European Copyright Society – Comment on Copyright and the Digital Services Act Proposal - Alexander Peukert; Martin Husovec; Martin Kretschmer; Péter Mezei; Jo\~ao Pedro Quintais (IIC - International Review of Intellectual Property and Competition Law, 2022)
On 15 December 2020, the European Commission submitted a proposal for a regulation on a single market for digital services (Digital Services Act, DSA) and amending Directive 2000/31/EC. The legislative project seeks to establish a robust and durable governance structure for the effective supervision of providers of intermediary services. To this end, the DSA sets out numerous due diligence obligations of intermediaries concerning any type of illegal information, including copyright-infringing content. Empirically, copyright law accounts for most content removal from online platforms, by an order of magnitude. Thus, copyright enforcement online is a major issue in the context of the DSA, and the DSA will be of utmost importance for the future of online copyright in the EU. Against this background, the European Copyright Society takes this opportunity to share its view on the relationship between the copyright acquis and the DSA, as well as further selected aspects of the DSA from a copyright perspective.
Keywords: 340; Digital Services Act; Copyright; Digital single market directive; Intermediary liability; Search engine; Online platform